The effect of intumescent mat on post-fire performance of carbon fibre reinforced composites. (May 2019) - Zhu, Chenkai; Li, Jingjing; Clement, Mandy; Yi, Xiaosu; Rudd, Chris; Liu, Xiaoling
This study investigated the effect of intumescent mats (M1 and M2) with different compositions on the post-fire performance of carbon fibre reinforced composites. The sandwich structure was designed for composites where M1 (carbon fibre reinforced composite-M1) or M2 (carbon fibre reinforced composite-M2) mats were covered on the composite surface. A significant reduction in the peak heat release rate and total heat release was observed from the cone calorimetric data, and carbon fibre reinforced composite-M1 showed the lowest value of 148 kW/m 2 and 29 MJ/m 2 for peak heat release rate and total heat release, respectively. In addition, a minor influence on mechanical properties was observed due to the variation of composite thickness and resin volume in the composite. The post-fire properties of composite were characterised, and the M1 mat presented better retention of flexural strength and modulus. The feasibility of two-layer model was confirmed to predict the post-fire performance of composites and reduce the reliance on the large amounts of empirical data.